INSTITUSIONALISASI AKAD MUAMALAH (Studi Transformasi tentang Proses dan Alur Migrasi Akad Personal ke Akad Institusi dalam Perbankan Syariah) - Ali Amin Isfandiar (JURNAL PENELITIAN, 2009)
Islamic contract mechanism, as it's called al-'aqd al-muamalah) was done as personal contract. The emerging of islamic bank makes it transfrormed being an institution contract, that changes a simple contract being a rigid one, because a position of the islamic bank. This process is called by "institutionalization", where it could be realized without external power which support that process, such as policy power who arranges by rules, internal resources who prepars software, hardware and brainware, economi power who supports market acceptance analysis, social power who supports accelerated improvement and inovation, and ijtihad power who supports syariah compliance. The three latest are research focus and by social economic approach and qualitative analysis model, this research finds that the institutionalization of islamic contract has been transforming for a long-long time ago and using two ways scientifically integration process, economics and syariah (islamic law), especially al-fiqh al-mu'ámalah.